2018
DOI: 10.1002/mnfr.201800232
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Fermentation Behavior of Isomalto/Malto‐Polysaccharides Using Human Fecal Inoculum Indicates Prebiotic Potential

Abstract: ScopeThis study characterize intestinal fermentation of isomalto/malto‐polysaccharides (IMMPs), by monitoring degradation of IMMPs, production of short chain fatty acids (SCFAs), lactic acid, and succinic acid as well as enzyme activity and microbiota composition.Methods and resultsIMMP‐94 (94% α‐(1→6) glycosidic linkages), IMMP‐96, IMMP‐27, and IMMP‐dig27 (IMMP‐27 after removal of digestible starch segments) are fermented batchwise in vitro using human fecal inoculum. Fermentation digesta samples are taken fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
74
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 70 publications
(90 citation statements)
references
References 48 publications
(73 reference statements)
3
74
0
Order By: Relevance
“…Total DNA was extracted from the stool samples, as previously described, using the double bead‐beating procedure followed by the QIAamp DNA stool mini kit (Qiagen, Hilden, Germany) according to the manufacturer's instructions. The resulting DNA templates (5–20 ng) were used for subsequent PCR amplification and Illumina HiSeq sequencing of the V4 region of 16S ribosomal RNA (rRNA) genes …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Total DNA was extracted from the stool samples, as previously described, using the double bead‐beating procedure followed by the QIAamp DNA stool mini kit (Qiagen, Hilden, Germany) according to the manufacturer's instructions. The resulting DNA templates (5–20 ng) were used for subsequent PCR amplification and Illumina HiSeq sequencing of the V4 region of 16S ribosomal RNA (rRNA) genes …”
Section: Methodsmentioning
confidence: 99%
“…The resulting DNA templates (5-20 ng) were used for subsequent PCR amplification and Illumina HiSeq sequencing of the V4 region of 16S ribosomal RNA (rRNA) genes. [18]…”
Section: Dna Extraction Pcr and Sequencingmentioning
confidence: 99%
“…In all samples combined across all treatment groups and time points, 39% of all expression data came from the genus Bacteroides and 27% from unclassified Enterobacteriaceae. Overall, the relative abundance of different bacterial groups based on the metatranscriptome data corresponded to the pattern in the relative abundance of different taxa based on the 16S rRNA gene analysis described previously by Gu et al [381] (Figure 2). (Gu et al, unpublished).…”
Section: Community Structure and Activity Patternssupporting
confidence: 83%
“…One of the aims of this study was to better understand the functional dynamics of the bacterial communities during IMMP degradation. Previously reported HPAEC and HPSEC analyses [381] showed that the degradation of IMMP-94 and IMMP-96 occurred between 12 h and 24 h of the incubation. At 24 h and 48 h we noted an increase in the expression of genes coding for enzymes that might be directly involved in the hydrolysis of α-(1→6) glycosidic linkages, namely EC 3.2.1.10 -oligo-1,6-glucosidase, EC 3.2.1.11 -dextranase, and EC 3.2.1.33 -amylo-α-1,6-glucosidase ( Figure S7a,b).…”
Section: Microbial Groups Directly Involved In the Degradation Of Thementioning
confidence: 92%
See 1 more Smart Citation